Multiphase intrusion detection and revocation system for wireless sensor networks. (1st December 2008) - De Oliveira, Sergio; Nogueira, Jose Marcos; Wong, Hao-Chi
Wireless sensor networks are subjected to several types of attacks specially attacks of denial of service types (DoS). A previous work proposes a routing strategy that considers alternative routes aiming to increase the resilience to the intrusion and allow efficient intrusion detection. This paper shows a revocation approach to reduce the number of intruders and enable new detection phase after a new route establishment phase. After the revocation, new intruders can be detected and revoked by their turn, minimising its effects over the network. After some turns, all of effective intruders can be revoked. The performance of the proposed approach was verified by simulation studies.